KAJIAN STRATEGIS PENGEMBANGAN POTENSI EKOWISATA DI LEMBAH BALIEM SEBAGAI SUATU ALTERNATIF PENGELOLAAN PARIWISATA BERKELANJUTAN - BONI ASSO; IB ADNYANA MANUABA; I NYOMAN SUNARTA (Master Program of Environmental Science, Postgraduate Program of Udayana University)
An alternative that could contribute positively to the conservation of the environment is the development ofecotourism based on consistency in adopting its principles. As an initial step in the development of attractive ecotourismobject, ideally an inventory should be made first in order to avoid mistakes that could happen. Lembah Baliem area is sorich in potential ecotourism resources which, however, have not yet been managed on the basis of the concept ofecotourism approach. Based on such background this research accommodates the potential available in Lembah Baliemarea in order to learn the possibility of developing sustainable ecotourism there. The objective of this research is to knowthe potential for developing ecotourism, to learn the obstacles to be faced, and to set the strategy for the development ofecotourism resources to be adopted for Lembah Baliem.This research is conducted in Lembah Baliem area, which administratively belongs to the regency of Jayawijaya,Papua Province. The data used in this research include both qualitative and quantitative data in accordance with the needof the research. The data also include both the primary and secondary data. The sampling in this research is based on nontestdata collecting instrument, in which the data is obtained through interview, questionnaire, observation, and documentation. Finally, the data already collected is categorized, discussed and analyzed using the SWOT matrix underSHIP approach.The research identification result shows that Lembah Baliem area has fairly varied and natural ecotourism resources,such as: 8 caves, 8 location of festival shows, 3 historical monuments, 3 biggest likes, 4 mummies, 4 beautyfull panaromesite, The obstacles of Baliem Ecotourism development are distance, stakeholder participation, knowledge of ecotourismconcept still limited and the index of tourist visiting still low. Tourism development in Lembah Baliem still concerned tomass tourism management strategy. According the result could be concluded that the ecotourism potential to bedeveloped, bud the development blocked by accessibility and human resources, so it should be solve out by 11 strategicsolution. The handling of those obstacle need stakeholder involving base of sustainable ecotourism development, thengive priority for straight access to West Papua.